Nanostructuring of electron beams. (25th January 2019) - Shiloh, Roy; Lu, Peng-Han; Remez, Roei; Tavabi, Amir H; Pozzi, Giulio; Dunin-Borkowski, Rafal E; Arie, Ady
Abstract: The remarkable technological advancements that culminated in today's powerful electron microscope have enabled scientists to traverse into new regimes of the nanoworld. However, the versatility of this complicated optical beamline allows for more than just inspecting atoms: by shaping the electron beam, new and interesting phenomena are sought after by the interaction of shaped beams with matter. Here, we review the recent newly-emerged field of electron beam shaping by thin film interaction of nanostructures and by interaction with shaped electrostatic fields. This article is dedicated to our friend Wolfgang P Schleich on the occasion of his 60th Birthday. Since 2014, Wolfgang has collaborated with us within the framework of a Deutsch-Israelische Projektkooperation project (supported by the Deutsche Forschungsgemeinschaft) entitled 'Science and applications of electron wave-functions shaped and manipulated by engineered nano-holograms', during which many of the concepts that we present here were developed.